Clinical risk factors for Achilles tendinopathy: a systematic review. Issue 21 (November 2019) - van der Vlist, Arco C; Breda, Stephan J; Oei, Edwin H G; Verhaar, Jan A N; de Vos, Robert-Jan
Abstract : Background: Achilles tendinopathy is a common problem, but its exact aetiology remains unclear. Objective: To evaluate the association between potential clinical risk factors and Achilles tendinopathy. Design: Systematic review. Data sources: The databases Embase, MEDLINE Ovid, Web of Science, Cochrane Library and Google Scholar were searched up to February 2018. Eligibility criteria: To answer our research question, cohort studies investigating risk factors for Achilles tendinopathy in humans were included. We restricted our search to potential clinical risk factors (imaging studies were excluded). Results: We included 10 cohort studies, all with a high risk of bias, from 5111 publications identified. There is limited evidence for nine risk factors: (1) prior lower limb tendinopathy or fracture, (2) use of ofloxacin (quinolone) antibiotics, (3) an increased time between heart transplantation and initiation of quinolone treatment for infectious disease, (4) moderate alcohol use, (5) training during cold weather, (6) decreased isokinetic plantar flexor strength, (7) abnormal gait pattern with decreased forward progression of propulsion, (8) more lateral foot roll-over at the forefoot flat phase and (9) creatinine clearance of <60 mL/min in heart transplant patients. Twenty-six other putative risk factors were not associated with Achilles tendinopathy, including being overweight, static foot posture and physical activity level. Conclusion: From an ocean of studies with high levels of bias, we extracted nine clinical risk factors that may increase a person's risk of Achilles tendinopathy. Clinicians may consider ofloxacin use, alcohol consumption and a reduced plantar flexor strength as modifiable risk factors when treating patients with Achilles tendinopathy. Trial registration number: CRD42017053258.